Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Kooperatif STAD pada Mata Pelajaran Instalasi Listrik - Afdal Zikri; Syaiful Islami (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Vocational high schools (SMK) play an important role in preparing students for the world of work. However, student learning outcomes in the subject of Electrical Lighting Installation at SMK Negeri 5 Kota Padang are still relatively low, with an average pretest score of 57.34. This study aims to test the effectiveness of the Student Teams Achievement Division (STAD) cooperative learning model in improving student learning outcomes. The research method used was classroom action research with 32 students from class XI TITL as subjects. Data were collected through pre-tests, post-tests, and observations of student activities during learning. The results of the study indicate that the implementation of STAD successfully improved student learning outcomes significantly, with an average post-test score of 82.19 and an N-Gain Score of 0.58 (moderate category). Academic achievement also increased from 15.6% to 75%. Further analysis revealed that collaborative interactions within groups, the reward system, and active student participation were key factors contributing to the success of this method. However, challenges such as time management and low student engagement require attention. It is concluded that the STAD model is effective in improving students' learning outcomes in the subject of Electrical Lighting Installation, both in terms of cognitive aspects and social skills. Therefore, it is recommended that teachers implement STAD with proper syntax and consider developing supporting media such as digital simulations to optimize the learning process.